Legal Aspects of Women's Political Participation in a Gender Perspective - Suryani, Ade Irma; Wardana, Dodi Jaya (Universitas Semarang, 2024)
This study aims to explore the legal aspects of women's political participation from a gender perspective, emphasizing the problem of the gap between regulation and implementation in legal practice in Indonesia, as well as the obstacles faced by women in achieving an equal position in politics. This study is motivated by the ongoing gap in political participation between men and women in various countries, including Indonesia, which can be seen from the lack of women in important decision-making at the local and national levels. Women's representation in the public sphere, especially in politics and decision-making, has been regulated in various regulations, such as the Election Law and the 30% quota Affirmative Action Policy. However, in practice, these regulations often do not achieve the expected goals due to structural and cultural obstacles, and minimal sanctions for non-compliance. This study finds that although there has been normative progress in building a legal framework that supports women's participation, its implementation is still weak due to various obstacles, including gender-biased legal interpretations, patriarchal dominance in the political system, and the lack of effective monitoring mechanisms. The main contribution of this study lies in the in-depth analysis of the gap between the regulation and practice of women's representation. Using a normative and sociological legal approach, this study offers a new perspective in understanding this problem, not only as a legal issue but also as a structural and cultural problem that requires multidimensional intervention. This study also provides concrete recommendations to strengthen law enforcement and ensure that affirmative policies can run effectively, such as improving legal sanctions, increasing the capacity of supervisory institutions, and ongoing gender education. Uniquely, this study contributes to the legal literature and practice by providing a comprehensive roadmap to address the gap in the implementation of affirmative policies in women's representation. Furthermore, this study emphasizes that improving the gender-responsive legal system is not only a normative need but also a prerequisite for creating substantive justice in Indonesian society.